Advances in algebra : (World scientific, 2003)
This is the proceedings of the ICM2002 Satellite Conference on Algebras. Over 175 participants attended the meeting. The opening ceremony included an address by R Gonchidorazh, former vice-president of the Mongolian Republic in Ulaanbaatar. The topics covered at the conference included general algebras, semigroups, groups, rings, hopf algebras, modules, codes, languages, automation theory, graphs, fuzzy algebras and applications.